Functional and structural alterations of cardiac and skeletal muscle mitochondria in heart failure patients - Guzmán Mantesana, Gustavo (2014)
Background and Aims: The fundamental mechanisms involved in the genesis and progression of heart failure are not clearly understood. The present study was conducted to analyze the cardiac mitochondrial involvement in heart failure, the possible parallelism between cardiac and skeletal muscle and if there is a link between clinical symptoms and mitochondrial damage. Methods: Left ventricle and pectoral biopsies were obtained from patients with heart failure (n: 21) and patients with inter-auricular communication as the unique diagnosis for surgery (n: 6). Mitochondria were isolated from these tissues and studied through electron microscopy, spectrophotometry to measure the activity of respiratory complex III and immunohistochemistry to determine the presence of reactive oxygen species. Results: More than 90% of cardiac and skeletal muscle mitochondria presented structural and functional alterations in relation to an increment in the reactive oxygen species production, even in patients without the presence of any clinical Framingham criteria. Conclusions: We demonstrated some parallelism between cardiac and skeletal muscle mitochondrial alterations in patients with heart failure and that these alterations begin before the major clinical Framingham criteria are installed, pointing to mitochondria as one of the possibly responsible factors for the evolution of cardiac disease.